Efficacy of Platelet-Rich Plasma for the Treatment of Interstitial Supraspinatus Tears: A Double-Blinded, Randomized Controlled Trial. Issue 8 (July 2019) - Schwitzguebel, Adrien J.; Kolo, Frank C.; Tirefort, Jérôme; Kourhani, Abed; Nowak, Alexandra; Gremeaux, Vincent; Saffarini, Mo; Lädermann, Alexandre
Background: The benefits of platelet-rich plasma (PRP) for the treatment of rotator cuff tears remain inconclusive, as it is administered either as an adjuvant to surgical repair or as a primary infiltration without targeting the index lesion, which could dilute its effect. Purpose: To determine whether PRP infiltrations are superior to saline solution infiltrations (placebo) at improving healing, pain, and function when injected under ultrasound guidance within isolated interstitial supraspinatus tears. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: In this single-center, double-blinded, randomized controlled trial, 80 adults with symptomatic isolated interstitial tears of the supraspinatus, confirmed by magnetic resonance arthrography, were randomized to PRP or saline injections. Each patient received 2 injections with a 1-month interval. The primary outcome was the change in lesion volume, calculated on magnetic resonance arthrography, at 7 months. The secondary outcomes were improvements in shoulder pain and the Single Assessment Numerical Evaluation (SANE) score at >12 months. Results: Preoperative patient characteristics did not differ between the 2 groups. At 7 months, there were no significant differences between the PRP and control groups in terms of a decrease in lesion size (–0.3 ± 23.6 mm 3 vs –8.1 ± 84.7 mm 3, respectively; P = .175); reduction of pain on a visual analog scale (VAS) (–2.3 ± 3.0 vs –2.0 ± 3.0, respectively; P = .586); and improvement in SANE (16.7 ± 20.0 vs 14.9 ± 29.0, respectively; P = .650), Constant (8.6 ± 13.0 vs 10.7 ± 19.0, respectively; P = .596), and American Shoulder and Elbow Surgeons (19.5 ± 20.0 vs 21.9 ± 28.0, respectively; P = .665) scores. At >12 months, there were no significant differences between the PRP and control groups in terms of a reduction of pain on a VAS (–3.3 ± 2.6 vs –2.3 ± 3.2, respectively; P = .087) or improvement in the SANE score (24.4 ± 27.5 vs 23.4 ± 24.9, respectively; P = .846). At 19.5 ± 5.3 months, the incidence of adverse effects (pain >48 hours, frozen shoulder, extension of lesion) was significantly higher in the PRP group than the control group (54% vs 26%, respectively; P = .020). Conclusion: PRP injections within interstitial supraspinatus tears did not improve tendon healing or clinical scores compared with saline injections and were associated with more adverse events. Registration: NCT02672085 (ClinicalTrials.gov identifier).